Decision-making in the diagnosis and treatment of stroke-associated pneumonia. Issue 12 (28th September 2012) - Harms, Hendrik; Hoffmann, Sarah; Malzahn, Uwe; Ohlraun, Stephanie; Heuschmann, Peter; Meisel, Andreas
Abstract : Background: Stroke-associated pneumonia (SAP) is associated with impaired outcome in acute stroke patients. Current European and American guidelines for acute stroke care are lacking standardised recommendations for the management of SAP. We investigated current diagnostic and treatment practice for SAP in German stroke units (SU). Methods: We developed a standardised questionnaire including characteristics of SU, questions related to antibiotic treatment approaches of SAP and five case vignettes describing relevant clinical scenarios based on Centers for Disease Control and Prevention (CDC) criteria for 'clinically defined pneumonia'. All certified German SU were invited to take part in the survey. Results: The survey took place from April to August 2010. Of all 162 German SU contacted, 83 (51%) responded. Classification and regression trees analysis suggested that SAP was diagnosed on the basis of clinical criteria such as fever and stroke severity. Chest x-ray showed only limited influence on the diagnosis of SAP. C-reactive protein was frequently requested as additional diagnostic information (38–76%). Group 3 cephalosporines and (acyl-) aminopenicillins/β-lactamase inhibitors are the most frequently used antibiotics (46–60%) in empiric mono (58%) and combination (42%) therapy. A minority of SU (5%) use prophylactic antibiotic treatment. Standardised procedures are available in 61% of SU. Conclusion: Clinical criteria were the main determinants for SAP diagnosis. In contrast, chest x-ray—the central diagnostic item in CDC criteria—was of minor importance. Our survey demonstrates heterogeneous diagnostic and therapeutic strategies in German SU. Future studies need to establish and to evaluate standardised criteria for SAP care.